ENOS GLu298Asp POLYMORPHISM AND ATHEROSCLEROSIS IN PATIENTS WITH END-STAGE RENAL DISEASE - Ates, Kadir; Ilhan, Nevin; Kaman, Dilara; Ilhan, Necip; Yildirim, Hanifi (John Wiley & Sons Inc, 2009)
[Abstract Not Available]